The South China Sea : a crucible of regional cooperation or conflict-making sovereignty claims? / edited by C. J. Jenner and Tran Truong Thuy. - Jenner, C. J. (Christopher John); Tran, Truong Thuy (Cambridge University Press, 2016)
The history of the South China Sea is a catalyst of international cooperation and conflict. Security in the Indo-Asia-Pacific is largely governed by command of these strategic waters. More than half of global shipping transits the South China Sea, which also holds significant reserves of oil, gas and minerals as well as some of the largest fisheries in the world. Drawing on a team of field-leading researchers, Jenner and Thuy provide an empirical study of the global ocean's most contested sea space. The volume's four parts offer an insightful analysis of the significance of the South China Sea to the international order; sub-national agents of influence on relations between states; the disputes over sovereignty through the analytical prism of international law; and the conflictful region's prospects. The primary source-based conclusion elucidates the agency of history and strategy in the South China Sea.